SÁNCHEZ-MOMPEÁN, Sofía. The Prosody of Dubbed Speech. Beyond the Character’s Words. Cham, Switzerland, Palgrave Macmillan, 2020, 250 pp., ISBN 978-3-030-35520-3 - Mejías-Climent, Laura (Hikma, 2023)
-